Functional aspects of hybrid genome interaction : sex determination and gene expression regulation in the Squalius alburnoides complex - Pala, Irene Alexandra de Carvalho Braz dos Santos, 1981- (2008)
Tese de doutoramento em Biologia (Biologia Evolutiva) apresentada à Universidade de Lisboa através da Faculdade de Ciências, 2009.